Eldecalcitol prevented OVX-induced osteoporosis through inhibiting BMSCs senescence by regulating the SIRT1-Nrf2 signal - Kou, Yuying; Rong, Xing; Tang, Rong; Zhang, Yuan; Yang, Panpan; Liu, Hongrui; Ma, Wanli; Li, Minqi (Frontiers in Pharmacology, 2023)
Background: Aging and oxidative stress are considered to be the proximal culprits of postmenopausal osteoporosis. Eldecalcitol (ED-71), a new active vitamin D derivative, has shown a good therapeutic effect on different types of osteoporosis, but the mechanism is unclear. This study focused on exploring whether ED-71 could prevent bone loss in postmenopausal osteoporosis by regulating the cell senescence of bone mesenchymal stem cells (BMSCs), and explaining its specific mechanism of action. Materials and Methods: An ovariectomized (OVX) rat model was established and 30 ng/kg ED-71 was administered orally once a day. The weight of rats was recorded regularly. Micro-computed tomography (CT) and histochemical staining were used to evaluate bone mass, histological parameters, and aging-related factors. Rat BMSCs were extracted and cultivated in vitro. Aging cells were marked with senescence-associated β-gal (SA-β-gal) dyeing. The mRNA and protein levels of aging-related factors and SIRT1-Nrf2 signal were detected by RT-PCR, western blot, and immunofluorescence staining. The reactive oxygen species (ROS) levels were detected by DCFH-DA staining. Results: Compared with the Sham group, the bone volume of the OVX group rats decreased while their weight increased significantly. ED-71 prevented bone loss and inhibited weight gain in OVX rats. More importantly, although the expression of aging-related factors in the bone tissue increased in the OVX group, the addition of ED-71 reversed changes in these factors. After extracting and in vitro culturing BMSCs, the proportion of aging BMSCs was higher in the OVX group than in the Sham group, accompanied by a significant decrease in the osteogenic capacity. ED-71 significantly improved the BMSCs senescence caused by OVX. In addition, ED-71 increased the expression of SIRT1 and Nrf2 in OVX rat BMSCs. Inhibition of SIRT1 or Nrf2 decreased the inhibitory effect of ED-71 on BMSC senescence. ED-71 also showed a suppression effect on the ROS level in BMSCs. Conclusion: Our results demonstrated that ED-71 could inhibit the cell senescence of BMSCs in OVX rats by regulating the SIRT1-Nrf2 signal, thereby preventing bone loss caused by osteoporosis.